Exploring the Mechanism of Complex Lemon-Angelica Sinensis-Boswellia Essential Oil on Anxiety Disorders with Melasma Through Network Pharmacology and Experimental Validation - Xu Xu; Wang Shengdong; Liu Chang; Liu Liping (Journal of Women's Mental Health, 2025)
The incidence rate of melasma is notably high among patients with anxiety disorders. Aromatherapy primarily influences the physiological and psychological states of individuals through the inhalation or application of essential oils, thereby facilitating the treatment or alleviation of various conditions. This study aims to explore the action mechanism of complex lemon-angelica sinensis -boswellia essential oil (CEO) in treating anxiety disorders with melasma. We investigated the active ingredients, targets, and pathways of CEO in relation to anxiety and melasma using network pharmacology. We employed cell assays and conducted nebulized essential oil inhalation tests on CUMS mice to validate the intervention effects of CEO on anxiety. A total of 28 active components, including neryl acetate, 3-butenylphthalide and octyl acetate, and 26 cross-targets, such as ESR1, CCND1 and PIK3CA, were identified. GO and KEGG pathway analyses indicated that these cross-targets were primarily involved in endocrine regulation, cell proliferation, and apoptosis, specifically through PI3K/Akt signaling pathway and calcium signaling pathway. The experimental results demonstrated that CEO significantly reduced the secretion of NO, TNF-a and IL-6, as well as the mRNA expressions of ESR1, CCND1 and PIK3CA in cells compared to the inflammatory cell model. Furthermore, CEO notably decreased the forced swimming immobility time of mice and the levels of IL-1β, ESR1 and CCND1 in hippocampus when compared to model mice. These findings suggest that CEO may regulate ESR1, CCND1 and PIK3CA through its citral, 3-butylphthalate and neryl acetate, thereby influencing endocrine function, cell proliferation and apoptosis, inhibiting inflammation and anxiety-like behavior in CUMS-induced mice.
Keywords: Lemon - angelica sinensis - boswellia essential oil (CEO)